Novel Mutations in the Transcriptional Activator Domain of the Human TBX20 in Patients with Atrial Septal Defect - Monroy-Muñoz, Irma Eloisa (Biomed Res Int, 2015)
Background. The relevance of TBX20 gene in heart development has been demonstrated in many animal models, but there are few works that try to elucidate the effect of TBX20 mutations in human congenital heart diseases. In these studies, all missense mutations associated with atrial septal defect (ASD) were found in the DNA-binding T-box domain, none in the transcriptional activator domain. Methods. We search for TBX20 mutations in a group of patients with ASD or ventricular septal defect (VSD) using the High Resolution Melting (HRM) method and DNA sequencing. Results. We report three missense mutations (Y309D, T370O, and M395R) within the transcriptional activator domain of human TBX20 that were associated with ASD. Conclusions. This is the first association of TBX20 transcriptional activator domain missense mutations with ASD. These findings could have implications for diagnosis, genetic screening, and patient follow-up.